Metode Dakwah Dr. KH. Asep Saifuddin Chalim, MA di Pondok Pesantren Amanatul Ummah Pacet-Mojokerto - Reni Puspita Yanti; Bunyamin (Busyro : Jurnal Dakwah dan Komunikasi Islam, 2021)
In implementing the da'wah method in an Islamic educational institution such as the Islamic boarding school the figure of a cleric is an important role holder in determining success. A Kiai or leader of a boarding school is required to have the ability and intelligence in his role as a preacher so that the message of preaching is conveyed to the mad’ū effectively and efficiently and on target. Therefore researchers interested in conducting research on the Da'wah Method Dr. KH. Asep Saifuddin Chalim, MA. Based on the statement above, a question arises. How is the concept of Dr. dawah's method KH. Asep Saifuddin Chalim, MA? How is the application of the propaganda method Dr. KH. Asep Saifuddin Chalim, MA? And what obstacles are faced in applying the method of da'wah. In this study the authors used a qualitative method, with data analysis using symbolic interaction theory. And data collection techniques using analytic descriptive techniques, namely data collected in the form of words, images, documentation and not numbers. Obtained from the results of observation, in-depth interviews with sources and documentation that will produce interpretation for the author. According to the author's analysis, the da'wah method Dr. KH. Asep Saifuddin Chalim, MA in the Islamic Boarding School of Amanatul Ummah Pacet-Mojokerto through observation and research, the writer can conclude, that with morals and religious knowledge as well as always istiqomah in carrying out the practices of the Sunnah and always remembering the seven keys to success, all those dreamed of will be achieved mind.